A newly distinguished marine magnetotelluric coast effect sensitive to the lithosphere–asthenosphere boundary. Issue 2 (4th May 2019) - Wang, Shunguo; Constable, Steven; Reyes-Ortega, Valeria; Rychert, Catherine A
SUMMARY: The marine magnetotelluric (MT) method is a useful tool for offshore studies aimed at, for example, hydrocarbon exploration and the understanding of Earth's tectonics. Marine MT data are often distorted by coastlines because of the strong resistivity contrast between the conductive ocean and the resistive land. At mid ocean ridges, the resistivity of Earth's structure can be assumed to be two-dimensional, which allows MT data to be decomposed into a transverse electrical (TE) mode, with electric current flowing approximately along the ridge, and a transverse magnetic (TM) mode, with electric current flowing perpendicular to the ridge. We collected marine MT data at the middle Atlantic Ridge which exhibited highly negative TM-mode phases, as large as –180°, at relatively high frequencies (0.1–0.01 Hz). Similar negative phases have been observed in other marine MT data sets, but have not been the subject of study. We show here that these negative phases are caused by a newly distinguished coast effect. The TM-mode coast effect is not only a galvanic effect, as previously understood, but also includes inductive distortions. TM-mode negative phases are caused by the turning of the Poynting vector, the phase change of electromagnetic fields, and vertically flowing currents in the seafloor. The findings provide a new understanding of the TM-mode coast effect, which can guide our ability to fit the field data with the inclusion of coastlines, and reduce misinterpretation of the data in offshore studies. The study also shows that the TM-mode coast effect is sensitive to the depth and conductivity of the asthenosphere, an important feature of the Earth's interior that was the object of our Atlantic Ocean study.